ANALISIS KEMAMPUAN MEMBACA MELALUI METODE EJA DI PROGRAM KAMPUS MENGAJAR PADA KELAS I SD INPRES 4/82 TIMURUNG - Wildani Salsabila Rahim; Sri Hastati; Erwin Nurdiansyah; Erniati Erniati; Jumriati Jumriati (Universitas Negeri Makassar, 2023)
The formulation of the problem in this study is the low reading ability of students, which is formulated as follows: 1) How is the implementation of the spelling method in the campus teaching program in improving the reading ability of grade I students at SD Inpres 4/82 Timurung?, 2) How is the ability to read through the spelling method in campus program teaches first grade students of SD Inpres 4/82 Timurung?. This study uses a type of qualitative research. The time of the research was carried out from March to June 2022 at SD Inpres 4/82 Timurung for class I students. The instruments used in this research were observation, interviews, and documentation. The data analysis technique used is the triangulation method.The results of the study provide a solution for grade I students who are lacking in reading skills, namely by applying the spelling method in the reading process which is very effective because with the spelling method students are taught the sound of letters, spell word by word, words into sentences, so that students' reading skills can improve. This means that the spelling method is appropriate for dealing with students who have difficulty reading.Rumusan masalah dalam penelitian ini adalah rendahnya kemampuan membaca siswa, yang dirumuskan sebagai berikut: 1) Bagaimana pelaksanan metode eja di program kampus mengajar dalam meningkatkan kemampuan membaca siswa kelas I SD Inpres 4/82 Timurung?, 2) Bagaimana kemampuan membaca melalui metode eja di program kampus mengajar pada siswa kelas I SD Inpres 4/82 Timurung?. Penelitian ini menggunakan jenis penelitian kualitatif. Waktu penelitian dilaksanakan pada bulan Maret sampai Juni 2022 di SD Inpres 4/82 Timurung pada siswa kelas I. Instrumen yang digunakan pada penelitian ini adalah observasi, wawancara, dan dokumentasi. Teknik analisis data yang digunakan adalah triangulasi metode.Hasil penelitian memberikan solusi bagi siswa kelas I yang kurang dalam kemampuan membaca yaitu dengan menerapkan metode eja dalam proses membaca sangat efektif karena dengan metode eja siswa di ajarkan bunyi huruf, mengeja kata demi kata, kata menjadi kalimat, sehingga kemampuan siswa dalam membaca dapat meningkat. Artinya metode eja ini tepat diterapkan untuk menangani peserta didik yang berkesulitan dalam membaca.